Investigating factors influencing Malaysians’ intention on use mobile payments service - Liu, Jing Yi (2023)
Since the rapid development of communication technology and the popularity of smart terminal devices, mobile phones have become a new method of accessing the Internet in recent years. As the basic application of the Internet, mobile payment is also expanding in market size, providing consumers with a more convenient payment experience. In the process of using mobile payments, consumers will be faced with a number of different influencing factors based on their individual subjective views, concerns about network security, etc. The purpose of this paper is to examine the factors influencing consumers' willingness to use mobile payments based on understanding existing scholars' research on consumers' willingness to use mobile payments. The technology acceptance model is combined with the diffusion theory of innovation to examine the five factors that influence consumers' willingness to use mobile payment: perceived usefulness, perceived simplicity, perceived risk, compatibility, and subjective norms. An online survey of Malaysian consumers was conducted based on the theoretical study described above, and 217 reliable data were collected. An empirical analysis of the factors influencing the intention to use mobile payments is conducted using SPSS data analysis software. In the study, consumers' attitudes toward mobile payment were significantly positively influenced by perceived ease of use, perceived usefulness, perceived risk, and subjective norm; compatibility did not significantly influence consumers' attitudes toward mobile payment. Based on the results of the research, this paper provides marketing suggestions tailored to the development of mobile payments.